Oxypalmatine promotes apoptosis and protective autophagy in lung cancer cells via the PI3K/AKT pathway - Ge Qiao; Zhanghao Huang; Youlang Zhou; Jiahai Shi (Cancer Cell International)
Abstract Oxypalmatine (OPT), a small molecule alkaloid isolated from Phellodendron amurense, is a bioactive compound with promising anticancer potential. We evaluated the efficacy of OPT using four lung adenocarcinoma cell lines and four patient-derived organoid tissues. Additionally, the anticancer effects of OPT were further validated through in vivo experiments. We investigated the impact of OPT on apoptosis in the A549 cell line and observed that OPT induced apoptotic cell death. Subsequently, western blotting and transmission electron microscopy revealed that OPT promoted autophagy in A549 lung cancer cells. Through network pharmacology analysis, we identified the potential involvement of the PI3K/AKT signaling pathway in the action of OPT. Molecular docking studies with PIK3R1 and AKT1 suggested that OPT may directly interact with this pathway. Western blot analysis further confirmed that OPT resulted in the inactivation of the PI3K/AKT signaling cascade. Furthermore, treatment with the PI3K/AKT agonist SC79 partially mitigated the pro-apoptotic effects of OPT. Co-treatment with the autophagy inhibitor chloroquine (CQ) and OPT enhanced OPT-induced apoptosis in lung cancer cells, indicating that OPT triggers protective autophagy in lung cancer cells. Co-treatment with the autophagy inhibitor CQ markedly enhanced OPT-induced apoptosis, suggesting that inhibition of autophagy sensitizes cells to OPT. These findings highlight that OPT triggers a protective autophagy response, and that combining OPT with autophagy inhibitors such as CQ may serve as a more effective therapeutic strategy for lung cancer.